Respon Pertumbuhan dan Hasil Tanaman Kacang Tanah (Arachis hypogea L.) Akibat Perlakuan Varietas dan Dosis Pupuk Organik Cair Limbah Kulit Pisang Raja Bulu (Musa paradisiaca) - Ratu Afifani Sagara Mughni; Slamet Abadi; Kasdi Pirngadi (Jurnal Ilmiah Wahana Pendidikan, 2021)
The demand for peanuts increase every year has an impact to farmers, varieties and fertilizers greatly determines peanuts productivity in an area. This research aimed is to know the effect and right dosage of raja bulu banana peel liquid compost to peanut crop variety. This research has been conducted since March until June 2021 in Sukabumi. This research used randomized block design (RBD) with two factors. First treatment was peanut crop varieties and second treatment was dosage of raja bulu banana peel liquid compost. There are several varieties for first treatment that is Local variety (V0), Gajah variety (V1) and Garuda variety (V2). For second treatment each treatment was control or without dosage (P0), 25 ml (P1), 50 ml (P2) and 75 ml (P3) with three replications. The result was analyzed using analysis variance (ANOVA) and continued with DMRT. The result this research showed local variety with 75 ml raja bulu banana peel liquid compost dosage (V0P3) the highest in several parameters that was, amount of pods (12.82 pods), weight of pods (30.92 g), 100 grains weight (40.17 g), and amount of yield (3.52 ton/ha).